PROBLEMS OF THE AGREEMENT ON CUSTOMS VALUE OF GOODS AND TRANSFER PRICE IN FOREIGN ECONOMIC CONTROLLED OPERATIONS OF THE ENTERPRISES OF UKRAINE - Pryimak, I.I.; Kmit , V.M.; Hryshchyshyn, Y.V. (The actual problems of regional economy development, 2019)
With the integration of the national economy into the global economic space, significantly are growing the volumes of foreign economic operations, most of which are carried out between related enterprises. Such operations are at the same time the subject to customs control over the completeness and timeliness of payment of customs duties, as well as to the tax control over the observance of the “arm's length” principle for the purposes of calculation and payment of income tax. Due to the inconsistency of the method of determining the transfer price and the customs value of the goods, the price of the same operations may differ significantly that creates significant risks for both taxpayers and the budget. The purpose of the article is to evaluate the methodological differences in determining of the goods customs value and the transfer price in foreign economic controlled operations of Ukrainian enterprises and to develop proposals for their harmonization in order to ensure fair taxation and stable budget revenues. In the article is used a set of methods and techniques of scientific knowledge, in particular, the method of logical generalization, system analysis and synthesis, as well as grouping and comparison. In this article, main international and Ukrainian normative acts regulating the procedure for determining the customs value of imported goods and the price of controlled operations are analyzed. The comparison of the methods of the estimation of the goods customs value and transfer pricing is made, as well as the conclusions on the possibility of their harmonization are made. Despite the differences between tax and customs control over foreign economic controlled operations, the need for cooperation between customs and tax services to optimize their work in this area and to achieve fair taxation is substantiated. It is proved that an important instrument for reconciling transfer prices and the customs value of imported goods is the agreement on the negotiation of pricing in controlled operations. The scientific novelty of the obtained results lies in the further development of the areas of harmonization of the customs value of imported goods and the transfer price in foreign economic controlled operations. The practical relevance of the proposed approaches to reconciling the customs value of goods and transfer prices will allow enterprises to optimize the costs associated with the preparation of documentation on foreign economic controlled operations on the one hand and to increase the efficiency of customs and tax services in this area on the other hand.